Analisis Proses Identifikasi Karakteristik Siswa SD Negeri 2 Cipondoh Kota Tangerang - Magdalena, Ina; Joe, Caecilia Jilia; Yuliawati, Dea (TSAQOFAH, 2023)
Learning designers must be able to analyze the specific situations and circumstances of their students in order to plan learning. Because each student and class group has unique characteristics and abilities, treating them all the same will actually lead to less-than-ideal learning outcomes. Therefore, analyzing the characteristics of the students is one of the crucial stages in the process of important learning planning. where students at the elementary school level differ from those at the secondary school level in their characteristics. They think very differently, perceive things differently, and approach problems in very different ways. When a child is young, he or she has a strong propensity to imitate an idol. Teenagers, on the other hand, genuinely desire to be acknowledged as complete individuals who are adults who are capable of determining their own lifestyle. Play and education go hand in hand during childhood. Their right to play is sometimes curtailed by schools' heavy workload. As a result, they frequently exhibit laziness and boredom while studying in class due to the similar learning environment. As a result, the purpose of this paper is to talk about the significance of analyzing the early abilities of students in terms of their age, physical, psychomotor, academic, and attitude development. This stage ensures that the learning program is tailored to the needs of the students who will participate in the process.